THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CULTURE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE: A LITERATURE STUDY - Syarifin, Muhammad Hanif; Atmaja, Hanung Eka (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Performance as a company benchmark to increase its profitability. This study aims to determine the effect of organizational commitment, organizational culture and job satisfaction on employee performance. This research uses a literature study method with a qualitative approach. The research used secondary data, which totaled 20 journals with a period of 2018-2023. The results of the research show that a measure of employee commitment to the organization and vice versa will create a good organizational atmosphere. Organizational commitment can be viewed from a behavioral perspective, where commitment is characterized by consistent patterns of behavior. The higher an employee's level of organizational commitment to the organization, the more likely they are to demonstrate improved performance. Organizational culture plays a significant role in coordinating job-related matters and minimizing the occurrence of errors within the organization. For employees, a supportive organizational culture can contribute to the achievement of their individual goals, as it serves as an internal mechanism for aligning the company's operations with the employees. Consequently, a positive organizational culture fosters adaptation and enhances employee performance. Job satisfaction also holds considerable influence over various aspects of work, particularly in relation to improving job performance. An increase in job satisfaction tends to be accompanied by improved performance. These three variables namely, organizational commitment, organizational culture, and job satisfaction have been empirically proven to exert a significant impact on employee performance.